Is the outcome of elective vs non-elective patients undergoing transcatheter aortic valve implantation different?: results of a single-centre, observational assessment of outcomes at a large university clinic - Wundram, Steffen; Seoudy, Hatim; Dümmler, Johannes C.; Ritter, Lukas; Frank, Johanne; Puehler, Thomas; Lutter, Georg; Lutz, Matthias; Saad, Mohammed; Bramlage, Peter; Sathananthan, Janarthanan; Wood, David A.; et al. (BMC cardiovascular disorders, 2023)
Background: Transcatheter aortic valve implantation (TAVI) can either be conducted as an elective (scheduled in advance) or a non-elective procedure performed during an unplanned hospital admission. The objective of this study was to compare the outcomes of elective and non-elective TAVI patients. Methods: This single-centre study included 512 patients undergoing transfemoral TAVI between October 2018 and December 2020; 378 (73.8%) were admitted for elective TAVI, 134 (26.2%) underwent a non-elective procedure. Our TAVI programme entails an optimized fast-track concept aimed at minimizing the total length of stay to ≤ 5 days for elective patients which in the German healthcare system is currently defined as the minimal time period to safely perform TAVI. Clinical characteristics and survival rates at 30 days and 1 year were analysed.Results: Patients who underwent non-elective TAVI had a significantly higher comorbidity burden. Median duration from admission to discharge was 6 days (elective group 6 days versus non-elective group 15 days; p < 0.001), including a median postprocedural stay of 5 days (elective 4 days versus non-elective 7 days; p < 0.001). All-cause mortality at 30 days was 1.1% for the elective group and 3.7% for non-elective patients (p = 0.030). At 1 year, all-cause mortality among elective TAVI patients was disproportionately lower than in non-elective patients (5.0% versus 18.7%, p < 0.001). In the elective group, 54.5% of patients could not be discharged early due to comorbidities or procedural complications. Factors associated with a failure of achieving a total length of stay of ≤ 5 days comprised frailty syndrome, renal impairment as well as new permanent pacemaker implantation, new bundle branch block or atrial fibrillation, life-threatening bleeding, and the use of self-expanding valves. After multivariate adjustment, new permanent pacemaker implantation (odds ratio 6.44; 95% CI 2.59–16.00), life-threatening bleeding (odds ratio 4.19; 95% confidence interval 1.82–9.66) and frailty syndrome (odds ratio 5.15; 95% confidence interval 2.40–11.09; all p < 0.001, respectively) were confirmed as significant factors. Conclusions: While non-elective patients had acceptable periprocedural outcomes, mortality rates at 1 year were significantly higher compared to elective patients. Approximately only half of elective patients could be discharged early. Improvements in periprocedural care, follow-up strategies and optimized treatment of both elective and non-elective TAVI patients are needed.
Veröffentlicht: 10. Juni 2023
Gesehen am 25.07.2023